Potential land-use function conflicts of cultivated land for urban sustainable development: a case study in Yancheng City, China - Zhu, Nanyan; Ma, Quan; Ai, Jingwen; Zeng, Zhen; Zhou, Chunhua (Frontiers in Sustainable Food Systems, 2023)
Introduction The evaluation on the trade-off/synergy relationship of urban cultivated land-use function conflicts (CLUFCs) for improving the sustainability of cultivated land ecosystem is one of the solutions to coordinate the contradiction between land health and economic development and alleviate food crises, and achieve “zero hunger” in the United Nations Sustainable Development Goals (SDGs). Methods In this study, Yancheng City was taken as the research object, and the cultivated land ecological function (CLEF) was evaluated by the morphological spatial pattern analysis-minimum cumulative resistance (MSPA-MCR) model from the perspective of multi-objective coordinated development of cultivated land, and cultivated land productive function (CLPF) was evaluated by net primary productivity (NPP). In addition, combined with local indications of spatial association (LISA) analysis, the spatial trade-off/synergy relationship between CLPF and CLEF was quantified and analyzed. The spatial principal co-coordinates-redundancy analysis (SPCoA-RDA) was used to explore the influencing factors and mechanisms of CLUFCs. Results The results show that there are obvious spatial heterogeneity and aggregation distribution characteristics of CLUFCs in Yancheng City. Through SPCoA-RDA, it is found that the spatial differentiation of CLUFCs is the result of the combination of internal (population density, road network, and water network) and external (spatial spillover effect) driving factors. Discussion Based on these results, the study area was divided into eight types of cultivated land suitability zones under four aggregation relationships of CLUFCs. Comprehensively considering production, CLUFCs were evaluated by socio-economic and geo-spatial statistical dates, and strategies for guiding the coordinated development and sustainable management of urban cultivated land had been put forward. This study can provide a theoretical framework and certain feasible suggestions for the sustainable development and the transformation of cultivated land system in agriculture cities.